Exploring Teachers and Students’ Perceptions of Enhancing Speaking Skills Using the STIFIn Concept - Zulaiha, Siti; Ferdiyanto, Feri; Islam , Raudhatul (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
This study aimed to understand how teachers and students perceived the use of the STIFIn concept in improving students' speaking skills. The STIFIn concept, which was based on five types of human intelligence—sensing, thinking, intuiting, feeling, and instinct—was believed to help design more personalized and effective learning strategies. The study used a qualitative method with data collection techniques in the form of semi-structured interviews with teachers and students. Motivator Quran Darussalam, a high school Islamic boarding school, is located at the research site. The steps used to collect data included conducting interviews, making observations, and reviewing documents related to teaching speaking skills. Data reduction, data display, data condensation, and conclusion drafting are methods of data analysis. The results of the research were that the use of the STIFIn concept helped teachers to recognize the characteristics of students' intelligence and thus to adapt teaching methods more appropriately. Students also reported an improvement in their self-confidence and speaking skills following the implementation of the method. However, there were still some challenges in adapting the method to different types of student intelligence, which required in-depth training and understanding on the part of teachers. Overall, the STIFIn concept offered a new approach that could enrich language teaching in the classroom.